- - دکتر غلامرضا سلیمانى امیرى (تحقیقات مالی, 2003)
In the present study the power of financial ratios for predicting financial crisis in Iranian Companies has been investigated. This paper employs multivariable regression model to deduce a model for predicting financial crisis in registered Companies of Tehran Stock Exchange (TSE) by using financial ratios. The initial sample was composed of 60 corporations, 30 firms in each group. (The distressed group and no distressed group). The variables were classified into four standard ratio categories, including liquidity, profitability, debt and assets management .The result showed that financial ratios were strong indicators for identification of financial distress in TSE companies. The predictability test of the model indicated that the model could predict financial crisis up to three years prior to this occurrence in a company.